1991
DOI: 10.1071/rd9910671
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of immunoactive inhibin in serum during human pregnancy: evidence for an ovarian contribution

Abstract: Immunoactive inhibin (ir-inhibin) concentrations in maternal serum during normal human pregnancy have been established in two separate studies employing cross-sectional and longitudinal sampling regimes. Ir-inhibin concentrations rose from the mid-luteal phase (geometric mean + 95% confidence intervals 1.490 (1.086-2.028) U mL-1) to peak at week 11 of gestation (3.77 (3.26-4.35) U mL-1), declined to a plateau from 14 to 25 weeks with means ranging from 1.8 to 2.3 U mL-1, and subsequently rose slowly to a peak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Previously reported comparative studies of conceptions on donor egg programs have been in conflict about the source of ir-inhibin; McLachlan et al [17] reported similar levels of ir-inhibin in the maternal circulation of pregnant women with functional ovaries and those conceiving with donor eggs, whereas a study by Yohkaichiya [18] showed decreased levels in women pregnant without corpus luteum function. Both these studies used an RIA for ir-inhibin that cannot distinguish between the free alpha subunit monomer and the dimeric inhibin forms.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previously reported comparative studies of conceptions on donor egg programs have been in conflict about the source of ir-inhibin; McLachlan et al [17] reported similar levels of ir-inhibin in the maternal circulation of pregnant women with functional ovaries and those conceiving with donor eggs, whereas a study by Yohkaichiya [18] showed decreased levels in women pregnant without corpus luteum function. Both these studies used an RIA for ir-inhibin that cannot distinguish between the free alpha subunit monomer and the dimeric inhibin forms.…”
Section: Discussionmentioning
confidence: 94%
“…1493 5 ----· 9; i·\ corpus luteum as the major site of ir-inhibin production during the luteal phase of the menstrual cycle [14] and with Yohkaichiya's [18] study showing decreased levels of irinhibin in women conceiving without functional corpora lutea in an egg donation program, which utilized an RIA for inhibin that detects the alpha subunit as the free inactive monomer and as part of the biologically active dimers. Muttukrishna et al [6] found that after surgical first-trimester termination of pregnancy, serum levels of pro-aCcontaining inhibins fell only marginally (-20%) during 4 h following the procedure, indicating that the corpus luteum is the major source in early pregnancy.…”
Section: Ri-2mentioning
confidence: 96%
“…However, in view of the transient nature of the rise, it is possible that the sampling regime employed in the present study may have missed this increase. The failure of ovine maternal plasma ir-inhibin levels to rise in late gestation contrasts with the very significant increase in concentrations in the last trimester of human pregnancy [2,8,38], which is presumed to arise from a placental source [8]. Similarly, a rise in ir-inhibin concentrations has been observed in late gestation in rats.…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, a rise in ir-inhibin concentrations has been observed in late gestation in rats. Maternal ovariectomy demonstrated that this is a product of the maternal ovary associated with resumption of follicular activity in preparation to the postpartum estrus that occurs in this species [8]. The variations in the pattern of inhibin secretion in late gestation in different species may thus reflect the type of placentation as well as the reproductive strategies of each species.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation